[PS 04–03] LONG-TERM TREATMENT WITH N-NITRO-L-ARGININE METHYL ESTER (L-NAME) INCREASES ACTIVITY AND EXPRESSION OF NA+−CL−COTRANSPORTER TO CAUSE SALT-SENSITIVE HYPERTENSION. (September 2016) - WANG, CONGHUI; Leheman, Latapati; Liu, Beibei; Yeerbolaiti, Alimila; Kawakami-Mori, Fumiko; Hirohama, Daigoro; Fujita, Toshiro; Shimosawa, Tatsuo; Ogura, Sayoko
Abstract : Objective: Blood pressure is regulated both by vascular resistance and blood volume. Vascular resistance is controlled by vasoactive hormones such as angiotensin II, norepinephrine and Nitric oxide. Blood volume is mainly regulated by the kidney, how much of salt is excreted. Angiotensin II is known to regulate sodium channel to increase sodium uptake. Our group recently clarified norepinephrine also activate sodium channel (sodium chloride cotransporter: NCC) via epigenetic modulation (Nat Med 2011). The accumulating data strongly suggest that vasoactive substances are not only act on vasculature but also affect on sodium homeostasis. We hypothesized that blockade of Nitric oxide synthesis by L-NAME has a direct effect on sodium channels in the kidney. Design and Method: C57BL/6J Mice were treated with 8%NaCl (high salt; HS) or 8%NaCl +L-NAME (0.7 mg/10 ml). Blood pressure was measured by telemetry. The function of sodium channel was monitored by pharmacologically and molecular biologically. NCC was blocked by hydrochlorothiazide (HCTZ) and other sodium channel (epithelial sodium channels; ENaC) was blocked by amiloride. Their protein expression was evaluated by Western blot. Results: Low dose L-NAME or high salt loading alone did not induce blood pressure changes in the C57BL/6J mouse.However, the mice developed hypertension during co-treatment with low dose L-NAME and high salt loading. To determine which type of sodium channel is involved, we injected both amiloride and HCTZ into the mice to inhibit the function of ENaC and NCC, respectively. The sodium excretion profile in urine showed that the mouse responded to HCTZ than amiloride suggesting that NCC is activated by L-NAME and high salt diet. It was confirmed by western blot. Conclusions: These results highly suggest that NO activate NCC to lead to salt-sensitive hypertension. Further we will use NCC-/- mice to confirm the blood pressure changes by HS+L-NAME. And check out the possible signal pathway between NCC and Nitric Oxide.